Public key certificate privacy in VoNDN: voice over named data networks - Dogruluk, Ertugrul (2020)
Scenarios were scripted by the C++11 library in ndnSIM 2.6. The scenario implementations and required tools can be publicly accessible at the author’s GitHub account—https://git.io/JJqEw